Protection of the best interests of a child in the medical field (According to the legislation in force in Georgia) (Law and world, 2024)
International and Georgian legislation recognises the priority of protecting a child's best interests. While discussing any issues related to a minor, the discussion starts by considering the best interests. The present article relates to protecting the best interests of a child in the field of healthcare when receiving medical services and the exact allocation of functions and duties of the involved decision-making parties to provide guaranteed protection of the best interests of a child. Protection of the best interests of a child includes both the immediate identification of the possible child abuse fact and any long-term interest that may influence the child’s development and psycho-emotional state. A legal representative acting on behalf of a child mainly decides on the medical services provided to the minor. Each case will be evaluated individually to guarantee the protection of a child’s rights and best interest. However, before assessing the protection of a child’s best interests in the medical field, the concept of the child’s best interests will be discussed in general. Acting within the framework of the medical legislation, medical workers play the leading role in the process of providing medical services to minors. That is why the constant involvement of the healthcare system is necessary to eliminate the gaps and barriers under consideration. To ensure the balance between parental authority and the child’s autonomous decision-making, the individual case must be evaluated, and a unified objective must be established using a multidisciplinary approach. The standard research method of the record of medical legislation clearly shows the conflict of interest occurring when considering the best interests of a child and the inevitable violation of the child’s unconditional right to be heard. Keywords: medical law, best interest of a child, parental right, child autonomy, conflict of interest, medical services IntroductionThis article aims to discuss the protection of children’s rights and best interests in the medical field. To achieve this goal, the problematic aspects identified within the protection of the child’s best interest will be reviewed using teleological and normative research methods. By summarizing the theoretical and practical material, it will become clear what danger the strict adherence to the requirements stipulated by the medical legislation of Georgia can cause to the best interests and rights of minors in the medical field.The research topic is relevant despite the number of normative acts on children’s rights adopted worldwide. Different countries regulate issues related to children’s rights with additional legislative acts according to their jurisdiction. Receiving services in the medical field is associated with certain additional barriers for minors, in which case it is difficult to ensure a balance between parental authority and the child’s autonomous decision-making.The child’s best interest cannot be defined according to one general standard. However, it is possible to limit the scope of the content to the best interest and necessarily include a common goal for all decision-makers around the child. The general definition of the best interests of a child is close to the rights protected by the human constitution. The necessity of a separate code regarding the child is due to the best interests, the content of which is determined individually in each case. We can say that the general best interest narrows down to each case and is formed taking into account a particular child’s psycho-emotional, social, and economic situation.As for the protection of the best interests of a child in the medical field, the first chapter will discuss the difference in the contents of a child’s best interest within the framework of acceptable decisions on various issues. The subject of the research of this chapter is also the minor as a person receiving medical services and the child’s right to be heard, taking into account his/her age and other factors.The second chapter relates to protecting the child’s personal data and the parental right to receive any information about his/her minor child. In the same chapter, legislative exceptions will be discussed, considering the child’s opinion higher than the parent’s right to receive information about the health status of his or her minor child.The third chapter will discuss the procedure for deciding on medical services for the child in case of parental dispute and the role of the court and other participants. The subject of this study is to protect the best interests of a child in medical law so that parental right is not disproportionately restricted. The aspects discussed in the central part will make visible the barriers that accompany the provision of medical services to minors and the author’s vision regarding these challenges.1. Protection of the best interests of a child in the medical field1.1. Concept of the best interests of the childThe definition of the concept of the best interests of a child can be found in the Code on the Rights of the Child that includes welfare, safety, healthcare, education, development, public, moral and other interests[1] of a child, being prioritized in accordance with the Code, the Constitution of Georgia, the Convention on the Rights of the Child, its additional protocols and other international agreements of Georgia and the individual characteristics of a child, with his/her participation and by taking into account his/her opinion.On November 20, 1989, under the auspices of the United Nations, the General Assembly adopted such an important act as “The Convention on the Rights of the Child”.[2] “The Convention on the Rights of the Child is the first collection of children’s rights at the international level and it is mandatory that these rights be guaranteed for every child”, Georgia joined the Convention on the Rights of the Child in 1994 and took obligation on the protection of the rights stipulated in the Convention.[3]The general definition of the best interests of the child is generally close to the human rights protected by the Constitution. However, the development of a separate code regarding the child is conditioned by considering the best interest, the content of which is determined individually in each case. When discussing any case involving a minor, it is necessary to involve specialists specializing in children’s rights precisely to make decisions under the multidisciplinary approach. Naturally, the best interest of a child depends and differs on the issue under consideration, whether it will relate to the determination of his place of residence, limitation of the right of one of the parents, obtaining permission for the disposal of real estate, or receiving medical services. In each case, the court must evaluate the age and readiness of the child to exercise his right to participate and be heard, the arguments of the legal representatives regarding the issue under consideration and the conclusion made with the participation of the guardianship authority.According to the Civil Code of Georgia, a minor under the age of 7 is considered incapable,[4] and according to the definition of the Code of the Rights of Child, a child from the age of 10 up to the age of 18 is adolescent.[5] Article 8 of the same code establishes the right of a child to participate and have his/her opinion be heard and defines that the restriction of this right is inadmissible under his/her incapability.Mostly, the decision regarding the child is made by the parent due to his/her infancy; however, when we talk about the child’s right to be heard, here it is directly considered the hearing of his/her opinion and not to be conveyed by his legal representative. It is important to define the authority that may not be delegated to a representative, for example, “... in case of listening to a child personally, this right may not be delegated to a legal representative - a parent”.[6] The right to listen to the child by the representative loses its primary purpose, to have child’s opinion heard. Although the representative should act in the child’s best interest and take part in the case, considering the child’s opinion is the only authority that would not be justified to be fulfilled by the representative.The research subject relates to protecting the minor’s best interest in the medical field and his/her right to be heard and participate. One point is to protect the child’s right to be heard about the decision about him, and another important issue is that the misinterpretation of the reply should not harm his/her best interest instead of protection.1.2. Minor receiving medical servicesAn essential condition for receiving medical services is obtaining informed consent from the patient, the signatory of which must be a competent person. If the patient is a minor, the medical institution receives informed consent from the legal representative, who is authorized to make a decision on the medical services to be provided to the minor.[7] In this regard, it is worth noting as to how much the decision taken by the legal representative regarding a specific medical intervention corresponds to the best interest of the minor, taking into account the expected results, complications, refusal of the intervention and all the circumstances that the medical institution informs the legal representative. Although the meaning of the legal representative in its content implies protecting the interest of the trustee and acting for his benefit, the content of its concept cannot guarantee that consent was given in the child’s best interest. Court approval has become mandatory[8] for the disposal of real estate registered in the name of a minor to protect the minor’s property interest pursuant to the high standard. The research topic relates to the health, life and development of minors, and the decision made against him/her might have a fatal impact.Since the medical institution provides medical services for minors, all individual cases related to minors should be reviewed with the involvement of specialized personnel. For example, the removal of a minor’s glands may not result in a violation of the child’s best interests, as will the removal of an organ related to fertility, for which there must be superior best interest protection. Of course, the most important factor is medical testimony, which became the basis for conducting any manipulation.At the same time, in the law on the patient’s rights, we find an exceptional record related to the age of a minor, which will be referred to in detail below and is related to the conscious psycho-emotional state of the minor patient. Accordingly, it turns out that despite the unlimited right of a child to be heard provided by the Code on the Rights of Child, it is justified to set a certain age limit when considering a minor’s opinion in medical services.In the medical field, the child’s right to be heard should not be solely determined under the age factor, as it depends on various circumstances, including the child’s level of maturity, the ability to understand the situation and the potential impact of medical intervention. Although age may be a factor in determining a child’s ability to participate in decision-making, it should not be the only criterion. Approach taking into account the child’s cognitive and emotional development coincides with Gillick’s concept of competence, which recognizes that children who have sufficient knowledge and intelligence to make decisions about their medical treatment should have the right to do so, regardless of their age.[9]For instance, in England and Wales, an adolescent over 16 is deemed competent to consent to medical treatment. A child below the age of 16 can be considered legally competent to consent to medical treatment if he or she is capable of understanding what is proposed and expressing his or her own wishes. It is primarily the task of the treating physician to assess if a child has sufficient understanding and intellectual maturity to understand a medical treatment, particularly its risks. Similarly, the act of Scotland provides that a child under the age of 16 has the legal capacity to consent to medical treatment if, in the opinion of a qualified medical practitioner attending him, he is capable of understanding the nature and possible consequences of the procedure or treatment.[10]Healthcare professionals and other involved persons, preferably including a team specializing in children’s rights, should engage with children and adolescents in age-appropriate communication, providing information in a way that is understandable to them. A child’s opinion should be considered alongside the opinions of their parents or legal guardians, recognizing that decisions about medical treatment often involve a balance between respecting the child’s autonomy and protecting their best interests. Joint decision-making should consider the common objective of both children and their legal representatives to protect the child’s best interest. If the child’s opinions conflict with the parents’ wishes or raise questions about their safety and well-being, healthcare providers may need additional support from both the guardianship authority and the court to ensure that decisions are made in the child’s best interests.2. Protection of child’s personal data2.1. Child’s personal data protection by medical institutionThe procedure and conditions for granting consent to the processing of data about a minor are prescribed by the legislation of Georgia that determines[11] the mandatory consent of a parent or other legal representative for the processing of data about a minor under the age of 16, except for cases directly provided by law. What is meant by the case stipulated by the law will be discussed in the given chapter. According to the same law, the consent of a minor, his parent or other legal representatives to data processing shall not be considered valid if it harms the minor’s best interests.[12]Consequently, the law considers the possibility that the consent given by the legal representative may harm the minor’s best interest.It should be noted that the law on patient rights provides for the authority of the parent and/or legal representative to receive complete information about the minor’s health condition.[13] The law on the protection of personal data requires the consent of the minor's legal representative for minor’s data processing, therefore, when considering such category of minor’s personal information, such as health status, we return to the consent of his/her legal representative.Within the framework of decision-making by a minor on his/her health condition, it is necessary to establish the age limit mentioned in the first chapter, and exactly under this condition, the Law on Patient Rights establishes an exception regarding the provision of information to the parent/legal representative, if a minor patient between the ages of 14 and 18, who, in the opinion of a medical service provider, correctly assesses his health condition and who has consulted a doctor for the treatment of a sexually transmitted disease or drug addiction, for consultation on non-surgical methods of contraception or for artificial termination of pregnancy.[14] In other cases, the parent has the right to receive complete information about the medical services related to his minor child.In addition, the issue of assigning responsibility to the medical service provider must be noted within the framework of the doctor’s independent decision on whether his minor patient is in a conscious state and whether he correctly assesses his health condition. For this purpose, it would be appropriate to involve a medical institution and a social worker specializing in children’s rights, who, based on the consultation with the child, would be able to determine whether the minor patient assesses his health condition correctly and whether his decision serves to protect the best interest. To achieve this goal, the organization of special, multiple training by healthcare representatives would help the staff working with minors obtain additional information.Accordingly, a legal record related to the provision of medical services adapted to minors has been developed in the field of healthcare, which puts the best interest of the minor above the rights of the parent. The decision on which right is superior in a specific case is the responsibility of the medical institution, the doctor, as a binding link in the relationship before dispute arises.The authority of a legal representative provided for by the law is based on the assumption that parents act in the best interests of their children and have a right to receive information about the child’s health and treatment. If there is a conflict between a child’s privacy protection and providing information to parents, the potential risks and benefits of disclosure should be carefully considered. Factors subject to consideration may include the child’s age and maturity level, the nature of disclosed information, the relationship between the parent and child and any other obligations regarding the child's safety or welfare.The safety and welfare of the child must be prioritized above all other considerations. Finally, establishing a balance between the child’s information privacy related to health and the parent’s right to information accessibility requires careful consideration of each case’s unique circumstances and a commitment to promoting the child’s best interests by respecting their autonomy and privacy.3. Protecting the best interest of a child in the event of a dispute between legal representatives3.1. The role of the medical institution and the court in case of a dispute between the child’s legal representatives Based on the subject of dispute, a child’s best interest is different in case of a dispute between the parents. The article’s central part discusses the medical institution’s role as a link between the minor patient and the parent. The psycho-emotional condition of a minor patient, the medical service, its evidence and necessity must be evaluated within the competence of a doctor. And any decision should be made considering the minor’s best interest.The issue of protecting the best interests of the child becomes complicated when parents argue regarding the treatment of their child and one of the parents addresses the court. Of course, the court cannot individually decide on such a category case; what is better - to protect the child’s best interest, conditionally, to continue the treatment in Georgia or to grant permission for the departure abroad? The court may consider the medical institution’s report as evidence of essential importance for making a decision; however, in case of a dispute between parents, the child’s decision-making autonomy is even more violated.The medical institution also has the right to appeal to the court in such cases: “If the decision of a relative or a legal representative of the patient who is a minor or unable to make a conscious decision is against the health interests of the patient, the medical care provider may appeal the decision to a court”.[15] Guardianship and custodianship authority are involved in such category cases to have made acceptable decisions in a complex manner. A child’s best interest regarding the right decision about his health status is violated.The medical institution exercises this right when it is clear that the parents’ disagreement affects a child’s best interest and medical intervention is unavoidable. In such a case, the doctor needs decision-making authority and immediate response.According to the amendment to the Civil Procedure Code of Georgia, a judge, lawyer, social worker, and/or other relevant specialist is invited to consider the needs of the minor and participate in the process related to the protection of the minor’s rights.[16] This implies the use of a multidisciplinary method, the participation of specialists who know the stages of the child’s development and will be able to select the right questions and analyze the answers given, considering their age and psycho-emotional attitude.If a medical institution applies to the court with a request to decide on the method of treatment of the child and there are different opinions of the parents and/or a conflict of interests between the parent and the child, the court should request the involvement of the guardianship and custodianship authority as the representative of the minor. At this time, a guardian appointed by the court is entitled to exercise representative authority to protect the child’s best interest.[17]In the case subject to consideration, when the medical institution applies to the court, it is natural that the situation requires an immediate decision. In such a case, the child’s right to be heard may be objectively impossible, depending on his medical testimony. At this stage, the court has imposed the most important function of evaluating the factual circumstances and evidence presented in favour of a child’s best interest. This is when the decision will have a long-term or permanent impact on the child’s future or development.ConclusionMinor should enjoy all the rights defined for the patient in the healthcare system in accordance with the established procedures determined by the legislation. Currently, the legislation contains all the normative records that lead to the protection of the best interest of a child. However, more specialized personnel are needed to balance the necessary intervention by the parent and/or legal representative and the autonomy of the child’s rights.To achieve this goal, the analysis of the child’s best interest as a general concept is described in the first chapter. On this basis, we can say that the general best interest is narrowed down to each case and is formed considering a particular child’s psycho-emotional, social, and economic situation. A multidisciplinary method is used for a detailed study of acceptable decisions around the child, which involves the participation of persons specialized in relations with minors.The central part of the topic refers to all the stages of medical services to be provided for the child, including informed consent and conducting a simple consultation or surgical intervention. The research topic was the protection and consideration of the best interests of a child at all stages of the mentioned process. The central part clearly shows the legal assumption arising in the introduction that direct enforcement of all statutory provisions may not always serve to protect the child’s best interests. According to the author’s point of view, when considering individual cases, there is to be evaluated the relationship between the parent and the child, and the expected results of providing or nondisclosure of information to the parent, it is recommended to allocate additional specialized human resources for the proper evaluation of this process.Information about a child’s health status is a special category of personal information that may be processed/disclosed with the consent of the legal representative. However, the use of this record through direct meaning may harm the best interest of a minor if a parent and child are in conflict, and providing certain information to the parent may lead to the risk of possible abuse of a child.For this purpose, it would be advisable to involve a medical institution and a social worker specializing in children’s rights, who, based on the consultation with the child, would be able to determine whether the minor patient assesses his/her health condition correctly and whether his/her decision serves the protection of the best interest.The child’s right to be heard, as one of the fundamental rights, is reinforced by normative acts on children’s rights, and Georgian legislation also prioritizes this right. As a result of researching this topic, it should be said that according to the child’s age and psycho-emotional condition, the use of the child’s right to be heard must be decided in the medical field as well, and again and again, with the proper intervention of specialized persons, it is possible to draw a correct and appropriate conclusion regarding the child’s views. In the main part of the article, it is discussed that the realization of this right in the medical field has a specific character.To thoroughly protect the child’s health rights provided by the law, it is recommended to constantly retrain the personnel working in the field of health care in the direction of children’s rights, to allocate specialized staff for minor patients to achieve the common goal of protecting the best interest of the child together with the legal representatives.BibliographyLaw of Georgia, Civil Code of Georgia. 26/06/1997.Law of Georgia, Civil Procedure Code of Georgia. 31/12/1997.Law of Georgia, Code on the Rights of the Child. 20/09/2019.Convention on the Rights of the Child. 20/11/1989.Law of Georgia on Patient Rights. 05/05/2000.Law of Georgia on Personal Data Protection. 14/06/2023.Chanturia, L., Zoidze, B., Ninidze, T., Shengelia, R., Khetsuriani, J. Comment of the Civil Code of Georgia. Book V. Tbilisi: “Law”. (2000). See Dolidze, L. Procedural Legal Peculiarities of Family Disputes within the Context of Protection of Minors’ Interests (presented for granting Master’s Academic Degree). 2020.Burduli, I. Regarding the issue of disposal of real estate owned by a minor by a parent. 2020.Veit in Hau/Poseck. BeckOK BGB. 55. Ed. 2019. §1643 Rn. 24.European Journal of Pediatrics. (2022). What does the best interests principle of the convention on the rights of the child mean for paediatric healthcare. <https://link.springer.com/content/pdf/10.1007/s00431-022-04609-2.pdf><https://www.service-public.fr/particuliers/vosdroits/F1551?lang=en [09.03.2024]><https://www.unicef.org/georgia/ka/%E1%83%91%E1%83%90%E1%83%95%E1%83%A8%E1%83%95%E1%83%98%E1%83%A1-%E1%83%A3%E1%83%A4%E1%83%9A%E1%83%94%E1%83%91%E1%83%90%E1%83%97%E1%83%90-%E1%83%99%E1%83%9D%E1%83%9C%E1%83%95%E1%83%94%E1%83%9C%E1%83%AA%E1%83%98%E1%83%90>Footnotes[1] The Law of Georgia, the Code of the Rights of Child, Article 1. Legislative Herald of Georgia. <https://matsne.gov.ge/ka/document/view/4613854?publication=6> [19.03.2024].[2] The Convention on the Rights of the Child. (1989).[3] <https://www.unicef.org/georgia/ka/%E1%83%91%E1%83%90%E1%83%95%E1%83%A8%E1%83%95%E1%83%98%E1%83%A1-%E1%83%A3%E1%83%A4%E1%83%9A%E1%83%94%E1%83%91%E1%83%90%E1%83%97%E1%83%90-%E1%83%99%E1%83%9D%E1%83%9C%E1%83%95%E1%83%94%E1%83%9C%E1%83%AA%E1%83%98%E1%83%90>[4] Civil Code of Georgia. (1997). Article 12. Legislative Herald of Georgia. <https://matsne.gov.ge/ka/document/view/31702?publication=130> [19.03.2024].[5] Law of Georgia Child Rights Code. (2019). Article 3. Legislative Herald <https://matsne.gov.ge/ka/document/view/4613854?publication=6> [19.03.2024].[6] Veit in Hau/Poseck. BeckOK BGB, 55. Ed.. 2019. §1643 Rn. 24. See: Burduli, I. On the issue of disposal of real estate by the parent owned by a minor. 2020. 26.[7] Patients’ Bill of Rights. (2000). Article 22. Legislative Herald of Georgia. <https://matsne.gov.ge/ka/document/view/16978?publication=13> [19.03.2024].[8] Civil Code of Georgia. (1997). Article 183. Legislative Herald of Georgia. <https://matsne.gov.ge/ka/document/view/31702?publication=130> [19.03.2024].[9] This criterion is derived from the case Gillick v. West Norfolk and Wisbech Area Health Authority and Department of Health and Social Security: HL. 17 Oct 1985 - https://www.service-public.fr/particuliers/vosdroits/F1551?lang=en[10] European Journal of Pediatrics. (2022). What does the best interests principle of the convention on the rights of the child mean for paediatric healthcare. <https://link.springer.com/content/pdf/10.1007/s00431-022-04609-2.pdf>[11] Law of Georgia on Personal Data Protection. (2023). Article 7. Legislative Herald of Georgia. <https://matsne.gov.ge/ka/document/view/5827307?publication=0#DOCUMENT:1;> [19.03.2024].[12] Ibid.[13] Patients’ Rights Act. (2000). Article 40. Legislative Herald of Georgia. <https://matsne.gov.ge/ka/document/view/16978?publication=13> [19.03.2024].[14] Ibid.[15] Patients' Bill of Rights (2000), Consent. Article 25. Legislative Herald of Georgia. <https://matsne.gov.ge/ka/document/view/16978?publication=13> [19.03.2024][16] Civil Procedure Code of Georgia. (1997). Article 51. Legislative Herald of Georgia. <https://matsne.gov.ge/ka/document/view/29962?publication=166> [19.03.2024].[17] Chanturia, L., Zoidze, B., Ninidze, T., Shengelia, R., Khetsuriani, J. Comment on the Civil Code of Georgia. Book V. Tbilisi: “Law” (2000).See: Dolidze, L. Procedural Legal Peculiarities of Family Disputes within the Context of Protection of Minors’ Interests (presented for granting Master’s Academic Degree). 2020. 42.